Pengembangan Sumber Daya Manusia di SD IT Almunawwar Panyabungan Mandailing Natal - linamayasari siregar; irma surynai siregar; Nadia Syahida (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Schools are formal educational institutions in which there are teaching and learning activities in achieving national education goals. To be able to achieve the goals of quality and quality national education, one of the components needed is human resources. Therefore the development of human resources is fundamental for school managers. The purpose of this study is to find out the efforts made by the school to improve the quality of human resources at SD IT Almunawwar and explain the implications of HR development on quality development at SD IT AlMunawwar. This type of research is descriptive qualitative research. Data were collected by interview, observation and documentation methods. Data were analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The conclusions show (1) efforts made by the school to improve the quality of human resources at SD IT Almunawwar is to conduct teacher evaluations every week, namely on Saturdays. In addition, the school also provides guidance in the form of subject teacher deliberations (MGMP) per field of study. And held teacher working group (KKG) training for PAI teachers. (2) implications of HR development on quality development at SDIT Al-Munawwar can be seen from the programs developed at SDIT Al-Munawwar.